2017
DOI: 10.1177/1937586717713734
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intensive Care Unit Layout and Nurses’ Work

Abstract: Neonatal intensive care units (NICUs) remain one of the few areas in hospitals that still use an open bay (OPBY) design for patient stays greater than 24 hr, housing multiple infants, staff, and families in one large room. This creates high noise levels, contributes to the spread of infection, and affords families little privacy. These problems have given rise to the single-family room NICU. This represents a significant change in the care environment for nurses. This literature review answers the question: Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Single-family-room NICUs also have their disadvantages, however. This type of layout can potentially exacerbate the effects of the organizational problems described above, since it increases nurses’ workload and makes interaction among staff more difficult [36, 37]. It also gives parents fewer opportunities for mutually supportive contact with other parents [38] and may even increase parents’ sense of insecurity and stress [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Single-family-room NICUs also have their disadvantages, however. This type of layout can potentially exacerbate the effects of the organizational problems described above, since it increases nurses’ workload and makes interaction among staff more difficult [36, 37]. It also gives parents fewer opportunities for mutually supportive contact with other parents [38] and may even increase parents’ sense of insecurity and stress [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that nurses do not respond to all alarms but, in fact, integrate information from multiple sources in a heuristic fashion in their decision making [ 2 , 11 , 12 ]. Within the context of a private room, with limited visual oversight, increasing patient surveillance via technological means and the potential need to cover long distances to reach the bedside, the complexity associated with addressing alarm fatigue acquires new dimensions [ 13 ]. Surprisingly, limited research has been carried out on alarm management, the clinical relevance of alarms and the factors that modulate nurse responsiveness, especially for private room settings [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurse wards often contain major flows of people, medications, and supplies and thus require special attention in planning (Yi & Seo, 2012). Doede, Trinkoff, and Gurses (2018) reviewed the impact of single-family designs on nurses’ work in neonatal ICUs. Hua, Becker, Wurmser, Bliss-Holtz, and Hedges (2012) compared the effects of centralized and decentralized nurse wards on staff communication, quality of care, and patients’ health.…”
Section: Resultsmentioning
confidence: 99%